The SAGE handbook of the 21st century city - Hall, Suzanne (Suzanne M.); Burdett, Richard (Los Angeles SAGE Reference, 2018)
The SAGE Handbook of the 21st Century City focuses on the dynamics and disruptions of the contemporary city in relation to capricious processes of global urbanisation, mutation and resistance. An international range of scholars engage with emerging urban conditions and inequalities in experimental ways, speaking to new ideas of what constitutes the urban, highlighting empirical explorations and expanding on contributions to policy and design. The handbook is organised around nine key themes, through which familiar analytic categories of race, gender and class, as well as binaries such as the urban/rural, are readdressed.
Part 1: Questions of Definition: An Urban Compendium -- Part 2: Hierarchy: Elites and Evictions -- Part 3: Productivity: Over-investment and Abandonment -- Part 4: Authority: Governance and Mobilisations -- Part 5: Volatility: Disruption and Adaptation -- Part 6: Conflict: Vulnerability and Insurgency -- Part 7: Provisionality: Infrastructure and Incrementalism -- Part 8: Mobility: Re-bordering and De-bordering -- Part 9: Civility: Contestation and Encounter -- Part 10: Design: Speculation and Imagination.
Keywords: Urbanization; Sociology, Urban; Urban policy